Silicon alleviates salt and drought stress of Glycyrrhiza uralensis seedling by altering antioxidant metabolism and osmotic adjustment - Zhang, Wenjin; Xie, Zhicai; Wang, Lianhong; Li, Ming; Lang, Duoyong; Zhang, Xinhui (Journal of plant research, 2017)
This study was conducted to determine effect and mechanism of exogenous silicon (Si) on salt and drought tolerance of Glycyrrhiza uralensis seedling by focusing on the pathways of antioxidant defense and osmotic adjustment. Seedling growth, lipid peroxidation, antioxidant metabolism, osmolytes concentration and Si content of G. uralensis seedlings were analyzed under control, salt and drought stress [100 mM NaCl with 0, 10 and 20% of PEG-6000 (Polyethylene glycol-6000)] with or without 1 mM Si. Si addition markedly affected the G. uralensis growth in a combined dose of NaCl and PEG dependent manner. In brief, Si addition improved germination rate, germination index, seedling vitality index and biomass under control and NaCl; Si also increased radicle length under control, NaCl and NaCl—10% PEG, decreased radicle length, seedling vitality index and germination parameters under NaCl—20% PEG. The salt and drought stress-induced-oxidative stress was modulated by Si application. Generally, Si application increased catalase (CAT) activity under control and NaCl—10% PEG, ascorbate peroxidase (APX) activity under all treatments and glutathione (GSH) content under salt combined drought stress as compared with non-Si treatments, which resisted to the increase of superoxide radicals and hydrogen peroxide caused by salt and drought stress and further decreased membrane permeability and malondialdehyde (MDA) concentration. Si application also increased proline concentration under NaCl and NaCl—20% PEG, but decreased it under NaCl—10% PEG, indicating proline play an important role in G. uralensis seedling response to osmotic stress. In conclusion, Si could ameliorate adverse effects of salt and drought stress on G. uralensis likely by reducing oxidative stress and osmotic stress, and the oxidative stress was regulated through enhancing of antioxidants (mainly CAT, APX and GSH) and osmotic stress was regulated by proline.